BAGAIMANA TERPAAN MEDIA UNTUK INFORMASI COVID-19 MEMENGARUHI NIAT MAHASISWA MENERAPKAN PERLINDUNGAN KESEHATAN SELAMA PANDEMI - Amin, Kholidil; Hadisiwi, Purwanti; Suminar, Jenny Ratna (Interaksi: Jurnal Ilmu Komunikasi, 2022)
Covid-19 is a disease caused by the coronavirus outbreak that first appeared in Wuhan, China, and spread worldwide, including Indonesia. This situation made WHO decides the world is in a state of the pandemic. During the pandemic, the Indonesian people, including students, received much information or deliberately sought information related to Covid-19 in the mass media or social media, which were assumed to shape their perceptions, attitudes, and behavior in protecting their health. Using the construct of the theory of planned behavior to investigate how media exposure to Covid-19 information in mass media or social media affects student health-protective behavior in the face of a pandemic, the present study surveyed 159 students in Indonesia who were selected using the convenience sampling technique. The present study analyzed the data by applying partial least square-structural equation modeling (PLS-SEM) to evaluate the model and path analysis. The result from the PLS-SEM shows that the use of mass media and social media to obtain information on Covid-19 significantly positively predicts the intention to implement student health protection behaviors mediated by perceived behavioral control (PBC) but not by attitude and subjective norm. The result also shows that PBC only significantly predicts behavioral intention.